PELAKSANAAN ASESMEN DIAGNOSTIK NON-KOGNITIF DALAM MEMETAKAN KEBUTUHAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA KELAS X AKL 2 DI SMK NEGERI 2 SEMARANG - Sifa Sofiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of the research is to map students' learning needs in learning Indonesian through non-cognitive diagnostic assessments. Non-cognitive diagnostic assessments can facilitate learning and provide complete information as feedback for teachers, students and parents so that they can find out the results of the goals that have been set and can serve as a guide in determining strategies, approaches, techniques and methods in the learning process furthermore. In this research, students' learning needs were mapped in learning Indonesian, especially in the classroom. The research uses a qualitative approach. The results obtained were that students' learning needs based on interests and talents were in good condition, and students' learning needs based on learning styles were found to vary. namely 17 people need a visual learning style, 8 people need an auditory learning style, and 11 people need a kinetic learning style. Based on the results of the non-cognitive diagnostic assessment analysis, the Indonesian language teacher has created a learning preparation plan, process plan, content plan and ongoing evaluation steps.